Comparative Efficacy of Insulin, Biguanides and Sulfonylureas In The Glycemic Control of Newly Diagnosed Diabetes Mellitus Patients in Rajshahi, Bangladesh - Zaman, Md Saif Zaman; Hassan, Parvez Hassan; Islam, S M Shahinul Islam; Ullah, Md Anayet Ullah; Rabbani, Md Golam Rabbani (Journal of Bio-Science, 2023)
The goal of the present study was to examine how well three distinct kinds of anti-diabetic drugs- insulin, biguanides and sulfonylureas performed in Bangladeshi patients who had recently been diagnosed with diabetes mellitus. This was an observational study and carried out on 102 patients admitted in different hospitals in Rajshahi, Bangladesh during the study period. Majority (32.02%) respondents belonged to 51-60 years age group, followed by 41-50 years and the least >60 years age group viz. 7.19%. Female preponderance was noticed in the study population where 59.80% were females; whereas 40.20% males. Results of distribution of respondents based on residence and class of anti-diabetic medication use showed in insulin receiving group 66.67% were urban people and 33.33% were rural resident; biguanides receiving groups 64.71% were urban resident and 35.29% were rural resident; sulfonylureas receiving groups 58.82% were urban resident and 41.18% were rural residents. Data on participant’s lifestyle and smoking habit showed lifestyle of 65.70% patients were sedentary and 34.30% were active and according to smoking habit of the patients 14% were smokers while 86% were non-smokers. Family history of DM among the patients showed 17% had familial history and 83% did not have. Data showed that the patients taken insulin, biguanides and sulfonylurea as with BMI were mostly in 18.50 - 24.99 with p-value 0.621. Although no statistically significant difference was noticed among the groups regarding treatment response of three drugs (p = 0.252, 0.284, 0.675 for HbA1c, FBS and PPBS respectively) after 3 months follow-up of medication use and (p = 0.284, 0.323, 0.817 for HbA1c, FBS and PPBS respectively) after 6 months follow-up. However, p-value was not significant but insulin receiving patients had relatively better treatment response than biguanide receiving group than sulfonylurea receiving group at 3rd and 6th month. In insulin receiving group 90.19 % had desired glycemic control. In biguanide receiving group 76.47 % had desired glycemic control. In sulfonylurea receiving group 84.31 % had desired glycemic control. So it appears that insulin provides the best glycemic control followed by sulfonylurea and the biguanides are relativity less potent in glycemic control of newly diagnosed patients in our study area. In this study, the sample size was quite small, which may not represent the whole population and the research used purposeful sampling, which may have skewed the results. J. Bio-Sci. 31(1): 39-49, 2023